PARTISIPASI MASYARAKAT TERHADAP PERWUJUDAN GOOD GOVERNANCE DI DESA DAMAI KECAMATAN WATANG SIDENRENG KABUPATEN SIDENRENG RAPPANG - Zhilviana Sulaeman; Ahmad Mustanir; Andi Ilham Muchtar (PRAJA: Jurnal Ilmiah Pemerintahan, 2019)
Participation in the realization of good governance in Damai village of Watang Sidenreng district, Sidenreng Rappang regency. The population in this study amounted to 476 heads of families through the Slovin formula as a technique sampling. The technique of data collection used were observation, questionnaires, documentation and interviews. The technique of data analysis was simple regression analysis using a frequency table. Which has processed using a Likert scale with SPSS V21 analysis. The results of this study indicate that the most influential indicator in public participation was the implementation of participation at 69.6% and the lowest result was the participation indicator in making decision at 62.8%. The most influential indicator in good governance was the rule of law at 68.8% and the lowest result was openness at 48.8%, these results are found based on processed questionnaire data and SPSS V21.